The Spirituality of Christian Suffering: The Personal Cross in Early Modern Imagery and Devotion - von Achen, Henrik (Periskop – Forum for kunsthistorisk debat, 2023)
The essay offers a contribution to understand the paradox of Christian suffering in seventeenth-century Transalpine devotional texts and their illustrations. Outlining the basic components of a transdenominational ‘Spirituality of Christian sufferance’, expressed in both Catholic and Lutheran ascetic literature, it provides a hermeneutic approach to the early modern iconography of carrying one’s own cross in imitation of Christ. To imitate Christ was to align one’s suffering with his. While Catholics and Lutherans had somewhat different practices to obtain such alignment, it originated in the same basic will to suffer, to receive adversity and pain from God. The spirituality of Christian suffering was an attitude of patience by which the Christian dealt with the fact that earthly life was a valley of tears, for most people misery a given. To endure suffering in faith became an important spiritual devotion for all Christians, regardless of denominational differences. Based on Luke 9:23 and Matthew 10:38, suffering should be embraced as a gift, rejection of the world as a salvific act. The model of the suffering Christ should move the faithful to take up their own crosses willingly, and devoutly endure trials and tribulations in this short life to achieve everlasting glory. The spirituality had to be acquired, internalized, and for this both Catholic and Lutheran literature presented literary ‘Schools of the Cross’. Flowing from this spirituality, simultaneously expressing and shaping it, an iconography grew forth rendering the cross-bearing as the path to salvation, a spirituality whose fulfilment was, indeed, the “Patientia Victrix”.